Alcohol: taking a population perspective - Gilmore, William; Chikritzhs, Tanya; Stockwell, T.; Jernigan, D.; Naimi, T.; Gilmore, I. (2016)
Alcohol consumption is a global phenomenon, as is the resultant health, social and economic harm. The nature of these harms varies with different drinking patterns and with the societal and political responses to the burden of harm; nevertheless, alcohol-related chronic diseases have a major effect on health. Strong evidence exists for the effectiveness of different strategies to minimize this damage and those policies that target price, availability and marketing of alcohol come out best, whereas those using education and information are much less effective. However, these policies can be portrayed as anti-libertarian and so viewing them in the context of alcohol-related harm to those other than the drinker, such as the most vulnerable in society, is important. When this strategy is successful, as in Scotland, it has been possible to pass strong and effective legislation, such as for a minimum unit price for alcohol.